Optimalisasi Pelayanan Perencanaan Kapasitas Air Bersih di Perumda Air Minum Tirta Intan - Salwa Nurfaiziya; Nunung Runiawati; Anang Muftiadi (Universitas Medan Area, 2022)
Perumda Air Minum Tirta Intan as a public service provider company in meeting the needs of the community in Garut Regency carries out a production process according to the results of capacity planning that has been made, but the realization of the resulting product is not achieved and this is repeated every year. The purpose of the study was to determine the planning process for the company's clean water production capacity as well as the obstacles and problems that caused the production capacity not to be realized as an effort to optimize clean water services. The main theory is used in making the right decision by predicting the level of demand accurately, equating technological progress with sales volume, determining the optimum operational size, and building for change. Qualitative research methods and data collection techniques with literature studies and field studies are internships/observations, documents, and interviews conducted to the Production Sub-Section, Engineering Planning Sub-Section, Research and Development Sub-Section, and Subscription Relations Sub-Section. The results of the study indicate that the Perumda Water Drinking Tirta Intan is already quite good in terms of planning its production capacity, but there are still several aspects that need to be improved such as human resource problems, technical and non-technical leaks (illegal connections), infrastructure facilities that need to be updated, and anticipation of sources. new to meet the water needs of the community.